Perlindungan Hukum Terhadap Lahan Pertanian Berdasarkan Undang-Undang Nomor 41 Tahun 2009 - Andik Galih Suhirmawan; Didiek Wahju Indarta; Irma Mangar (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The change of agricultural land for food production into small plots threatens the sustainability of agriculture and food security. This study discusses the legal protection and effectiveness of its application in preventing land use change. The research uses a normative legal approach with legal and conceptual methods. The findings show that the legal rules are sufficient, but their implementation is not effective due to weak oversight and economic pressures. The conclusion is that there is a need to strengthen legal enforcement and support for farmers.